Measurement of Midwifery Clinical Leadership Among Nursing Students: Exploratory Factor Analysis - Chooha U; Chotwattanakulchai N; Sirisome J (Advances in Medical Education and Practice, 2022)
Umasawan Chooha,1 Nadsuda Chotwattanakulchai,2 Jirawun Sirisome1 1Department of Maternal-Newborn Nursing and Midwifery, Faculty of Nursing Rajamangala University of Technology Thanyaburi, Pathum Thani, Thailand; 2Department of Maternal-Newborn Nursing and Midwifery, Srisavarindhira Thai Red Cross Institute of Nursing, Bangkok, ThailandCorrespondence: Umasawan Chooha; Nadsuda Chotwattanakulchai, Email umasawan_C@rmutt.ac.th; nadsuda.c@stin.ac.thPurpose: The aim of this study was to report the development measurement of midwifery clinical leadership instruments among nursing students.Methods: Specifically, the five-component concepts defined by Katz and Standards Midwifery Practice were used to build items for midwifery clinical leadership instruments. This study also used Netemeyer’s “Guidelines in Scale Development” to develop an instrument for midwifery clinical leadership among nursing students. The sample used for the research was 9 experts and 330 nursing students in the fourth year of being selected by multi-stage sampling. The instruments used in the study were an interview guide and a questionnaire. The data were analyzed by content analysis and factor analysis (exploratory factor analysis: EFA).Results: Three separate data collections were used for the development of these instruments. The outcome of the content validity assessment was a 60‐items questionnaire, Item-Objective Congruence (IOC) 0.94. The results of EFA yielded an instrument with 58 items in four-component. The final value of the Kaiser–Meyer–Olkin (KMO) and Bartlett’s Test was 0.956.Conclusion: The instruments present a good interpretation of the data and were consistent with the personality attributes. The questionnaire was designed to measure with strong loading of measurement.Keywords: measurement, midwifery clinical leadership, nursing students